Depression is not the only cause of cognitive impairment in chronic migraine - N. V. Latysheva; E. G. Filatova; D. V. Osipova (Нервно-мышечные болезни)
Background. Patients with the chronic migraine frequently present with memory and attention complaints. However, the prevalence and phenotype of such impairment in chronic migraine have not been studied.Objective – to evaluate the prevalence of the objective cognitive deficit in patients with chronic migraine and factors underlying its etiology. Materials and methods. We recruited 62 subjects with chronic migraine and 36 genderand age-matched controls with low-frequency episodic migraine (not more, then 4 headache days per month) aged 18–59. All patients filled in the Hospital Anxiety and Depression Scale (HADS) and Sheehan Disability Scale. Cognitive function was assessed with the Montreal Cognitive Assessment (MoCA), Digital Symbol Substitution Test (DSST), Rey Auditory Verbal Learning Test (RAVLT), and the Perceived Deficits Questionnaire (PDQ-20).Results. In this study 58 % of patients with chronic migraine complained of memory loss. Cognitive impairment was also found with PDQ-20. Objectively, we found a significant decrease in 90-second DSST results and RAVLT total recall and learning rate. In 40 % of subjects with chronic migraine scored lower than 26 points on MoCA. Patients with chronic migraine more frequently had lower DSST rates as compared to episodic migraine (odds ratio 5.07 (95 % confidence interval – 1.59–16.17); p = 0.003). Depression and anxiety did not correlate with performance on cognitive tests. Chronic migraine (frequent headache) and longer headache history, but not depression, anxiety or medication overuse were independent predictors of cognitive impairment.Conclusion. Subjective and objective cognitive deficits are prevalent in the chronic migraine population. Most often memory and attention are impaired. Longer headache history and presence of chronic migraine are independent risk factors for cognitive impairment in patients with chronic migraine.